Cerium ammonium nitrate: A new catalyst for regioselective protection of glycols - Comin, Maria Julieta (2004)
The regioselective introduction of a methoxymethyl (MOM) group on different type of glycols via an orthoester intermediate was investigated. The novelty presented in this study is the use of ceric ammonium nitrate instead of the previously employed camphorsulfonic acid as catalyst. The monoprotection reaction was revealed to be highly selective when the glycol moiety was in the presence of an ether functionality.